VAT on imported services: Implications for the collective investment scheme industry in the absence of place of supply rules in South Africa - Ockhuis, Ivor (Department of Finance and Tax, 2017)
The main purpose of this study is to analyse the South African VAT implications for offshore investment via the CIS industry in the absence of detailed place of supply rules; more specifically, where the fees charged, in respect of services rendered to manage these funds, are consumed. This is accomplished by analysing the South African VAT legislation in order to determine whether it succeeds in providing certainty regarding the place of supply of offshore investments, and whether there is a VAT on imported services exposure in the CIS industry. This analysis highlights the problems associated with the limited place of supply rules in South Africa. Furthermore, this study also includes an analysis to establish whether place of supply rules exist in certain developed countries, with regard to offshore portfolio management services. These findings are compared to determine whether similar rules can be implemented in South Africa. Some foreign countries, like New Zealand, Canada and the member states of the European Union, do cater for specific place of supply rules and this is the reason for their selection. This study concludes that the place of supply rules identified in the South African VAT legislation are not sufficient to determine whether offshore portfolio management services are deemed to take place (consumed) in South Africa, and accordingly be subject to VAT in South Africa. The study further concludes that the place of supply rules recommended in the International VAT/GST Guidelines issued by the Organisation for Economic Cooperation and Development (OECD) and place of supply rules established in certain member states2 of the European Union indicate that portfolio management services should be taxed where the consumer is located. Should South Africa implement place of supply rules based on the European legislation and guidelines issued by the OECD, the problems associated with the absence of place of supply rules in South Africa can be resolved. This will ensure no competitive advantage gained for foreign or domestic service providers of portfolio management services.